2020
DOI: 10.5114/aic.2019.91309
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and determinants of stenosis recurrence after renal artery angioplasty in hypertensive patients with renovascular disease

Abstract: Introduction: Restenosis (RS) following percutaneous angioplasty (PTA) of renal artery stenosis (RAS) might have an unfavourable impact on renal function and blood pressure (BP) outcomes. Aim: To evaluate the prevalence and predictors of RS in patients treated with PTA for RAS, and the relationship between BP and renal function (RF) changes with RS. Material and methods: We analysed freedom from RS in 210 patients (age 64.6 ±12.8 years; range: 20-85), who underwent 248 successful stent-assisted PTAs in RAS. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Secondary damages due to resolved primary cause of arterial hypertension were prevented. Follow-up evaluation due to a recurrence rate of 20% is essential (6,7).…”
Section: Patient Perspectivementioning
confidence: 99%
“…Secondary damages due to resolved primary cause of arterial hypertension were prevented. Follow-up evaluation due to a recurrence rate of 20% is essential (6,7).…”
Section: Patient Perspectivementioning
confidence: 99%
“…Although, medical treatment is a first line management in patients with renovascular hypertension [4], recent population-based data show that blood lowering therapy is insufficient in about 30% of hypertensive patients leading to masked uncontrolled blood pressure elevations [7]. This blood pressure instability is most frequent in patients with cardiovascular comorbidities, and those who require multiple antihypertensive medications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although, systolic (SBP) and diastolic blood pressure (DBP) lowering following PTA for ARAS is associated with better outcomes, the effect of PTA on blood pressure response is difficult to predict [9,10]. For example randomized trials demonstrate mild or no advantage of PTA plus best medical therapy (BMT) over BMT alone in regard to blood pressure or renal function improvement in all-comers with ARAS [6,7,8,12]. On the other hand, observational studies reported potential advantage of PTA of ARAS in terms of cardiovascular death (CVD) and all-cause mortality risk decrease, blood pressure lowering or even hypertension cure [13,14,15].…”
Section: Introductionmentioning
confidence: 99%